Anomalous stepped-hysteresis and T-induced unit-cell-volume reduction in carbon nanotubes continuously filled with faceted Fe3C nanowires. (23rd February 2021) - Xia, JiaChen; Guo, Jian; Zhang, Xi; Lan, Mu; Wen, Jiqiu; Wang, Shanling; He, Yi; Xiang, Gang; Corrias, Anna; Boi, Filippo S
Abstract: Ferromagnetically-filled carbon nanotubes have been recently considered important candidates for application into data recording quantum disk devices. Achievement of high filling rates of the ferromagnetic materials is particularly desirable for applications. Here we report the novel observation of carbon nanotubes continuously filled along the capillary with unusual μ m-long faceted Fe3 C nanowires. Anomalous magnetic features possibly due to strain effects of the crystal facets are reported. Magnetization measurements revealed unusual stepped magnetic hysteresis-loops at 300 K and at 2 K together with an anomalous decrease in the coercivity at low temperature. The observed unusual shape of the hysteresis is ascribed to the existence of an antiferromagnetic transition within or at the boundary of the ferromagnetic facets. The collapse in the coercivity value as the temperature decreases and the characteristic width-enhancement of the hysteresis with the field increasing appear to indicate the existence of layered antiferromagnetic phases, possibly in the strain-rich regions of the nanowire facets. Zero field cooled (ZFC) and field cooled (FC) magnetic curves evidenced presence of magnetic irreversibilities, an indicator of a possible spin-glass-like behavior induced by competing antiferromagnetic and ferromagnetic interactions. Characterization performed with low temperature XRD measurements, further revealed a slight variation in the average Fe3 C unit cell parameters, suggesting the absence of additional unit-cell volume induced ferromagnetic transitions at low temperature.